Neutron detection by Gd-loaded garnet ceramic scintillators. (July 2019) - Dosovitskiy, G.; Karpyuk, P.; Gordienko, E.; Kuznetsova, D.; Vashchenkova, E.; Volkov, P.; Retivov, V.; Dormenev, V.; Brinkmann, K.-T.; Zaunick, H.-G.; Mechinsky, V.; Fedorov, A.; et al.
Abstract: Ceramic samples of (Gd, Y)3 (Ga, Al)5 O12 :Ce compounds were obtained by air sintering of uniaxially pressed powders, synthesized using a coprecipitation approach. The resulting material contained several percent of pores and was light scattering but translucent, with estimated light yield of 4.5 ph/keV under γ-ray excitation. The ceramic samples demonstrated the ability to detect neutrons from an Am–Be source – more than 70% of the signal was estimated to be caused by neutrons of energies exceeding 1 eV. Highlights: Translucent Gd-loaded garnet ceramic samples were obtained by air sintering. Estimated light yield was 4.5 ph/keV under γ-ray excitation. Neutron signal from an Am–Be source was detected. More than 70% of the signal was assigned to neutrons with energies exceeding 1 eV.